2021
DOI: 10.2967/jnumed.121.262821
|View full text |Cite
|
Sign up to set email alerts
|

PSMA PET Validates Higher Rates of Metastatic Disease for European Association of Urology Biochemical Recurrence Risk Groups: An International Multicenter Study

Abstract: The European Association of Urology (EAU) Prostate Cancer Guidelines Panel recommends risk groups for biochemically recurrent prostate cancer (BCR) to identify men at high risk of progression or metastatic disease. The rapidly growing availability of PSMA-directed PET imaging (PSMA PET) will impact prostate cancer staging. We determined the rates of local and metastatic disease in recurrent and persistent prostate cancer stratified by EAU BCR risk groups and biochemical persistence (BCP). Methods:Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Moreover, it is possible that the T stage and PSAdt determined a confounding effect on the BCP setting, due to the higher prevalence of T stages ≥ 3a in this subgroup (66% vs. 51% in BCR after SRT vs. 54% in first-time BCR), and the lower PSAdt (3.4 months vs. 9.0 in BCR after SRT vs. 8.3 in first-time BCR). The hypothesis of a predictive role of BCP in bone recurrence is supported by previous studies by Ferdinandus J. et al [ 30 ], Meijer et al [ 31 ] and Farolfi et al [ 32 ], in which high proportions (40%, 39%, and 33%, respectively) of BCP patients were found to already have distant metastatic localizations (≥miM1) at PSMA-PET. Moreover, in 2015 Bianchi et al [ 33 ] already reported skeletal/visceral metastases to be the first site of recurrence in up to ~50% of BCP patients with a history of node-positive PCa treated with RP and extended pelvic lymph node dissection (ePLND).…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, it is possible that the T stage and PSAdt determined a confounding effect on the BCP setting, due to the higher prevalence of T stages ≥ 3a in this subgroup (66% vs. 51% in BCR after SRT vs. 54% in first-time BCR), and the lower PSAdt (3.4 months vs. 9.0 in BCR after SRT vs. 8.3 in first-time BCR). The hypothesis of a predictive role of BCP in bone recurrence is supported by previous studies by Ferdinandus J. et al [ 30 ], Meijer et al [ 31 ] and Farolfi et al [ 32 ], in which high proportions (40%, 39%, and 33%, respectively) of BCP patients were found to already have distant metastatic localizations (≥miM1) at PSMA-PET. Moreover, in 2015 Bianchi et al [ 33 ] already reported skeletal/visceral metastases to be the first site of recurrence in up to ~50% of BCP patients with a history of node-positive PCa treated with RP and extended pelvic lymph node dissection (ePLND).…”
Section: Discussionmentioning
confidence: 55%
“…Next, additional late scans were restricted to the pelvis potentially missing extrapelvic metastases that would only have been visible on late imaging. Although the risk seems to be very low in the investigated cohort, distant metastases are possible even in low-risk cases [ 35 ]. To reduce the chance of missing relevant visceral or bone metastases, contrast-enhanced full-dose CT scans were performed whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…To assess more widely whether equipoise was present, we distributed an on-line survey to prostate cancer clinicians, consisting of primarily urologists and radiation oncologists [19]. We received 53 responses (58% urology, 40% radiation oncology) of diverse practice experience (median [range] 15 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] years). In all, 81% of those surveyed were supportive of 'deintensification' as a concept for management of PSA recurrence following RP.…”
Section: Trial Feasibilitymentioning
confidence: 99%
“…It has recently been publicly subsidised in Australia as a standard-of-care investigation following PSA recurrence/persistence after RP or definitive RT [11]. Notably, PSMA-PET/CT detects a higher rate of metastases in patients with EAU high-risk disease than low-risk disease [12,13] and ligand uptake is associated with prognostic factors including PSA, ISUP GG and PSA-DT in the setting of PSA recurrence [14]. Preliminary data evaluating the relationship between PSMA-PET/CT characteristics and SRT outcomes support the assertion that low or absent ligand expression is associated with enhanced favourable biology and clinical outcomes [15,16], representing a truly low-risk cohort of patients in whom surveillance may be preferable.…”
Section: Introductionmentioning
confidence: 99%